On the Scientific and Applied Practice of Behavior Analysts - Y.M. Erz (Moscow State University of Psychology and Education, 2021)
The description of contemporary trends in the development of behavioral analysis as an evidence-based practice in Russia is included in current special issue. A brief analysis of the content of thematic publications included in the issue is carried out. Readers will learn about studies that evaluate the effectiveness of a behavioral analytic intervention for changing socially significant behaviors by the implementation of single-object design: about the evaluation of the effectiveness of the use of direct and generalized conditional reinforcement (tokens); about the experimental evaluation of the impact of the PECS alternative communication system on the vocal initiatives of children with autism; about functional communication skills-based training (SBT), as well as about a new approach to assessing and correcting behavioral problems - functional analysis of synthesized contingencies based on interview (IISCA). I am confident that this issue of the journal is of interest to professionals and parents of children with problem behavior, and will contribute to the further development of research and practical activities of Russian behavioral professionals.